Položaj slovenskega govora skozi prizmo stavčne fonetike - aktualizacija opisa osnovnih besedilnofonetičnih parametrov - Tivadar, Hotimir (Jezik in slovstvo, 2018)
In the article, we explain and supplement the basic characteristics of Slovenian prosody (sentence phonetics) with new knowledge and research. We have conceived the basic textual phonetic parameters and phonetics as a special linguistic discipline that contributes to a better implementation of spoken texts. We critically discuss research by Toporišič and the normative principles of the Slovenian language, which have influenced the formation of contemporary Slovenian linguistics and public speech.
Keywords: barva glasu; besedilna fonetika; fonetika; jezikovna norma; knjižni jezik; premor; slovenščina; stavčna intonacija